Taste Masking: A Novel Technique for Oral Drug Delivery System - Kalaskar, R.; Singh, R. P. (Asian Journal of Pharmaceutical Research and Development, 2014)
Oral administration of pharmaceuticals is one of the most popular methods of drug delivery. Many orally administered drugs elicit bitter taste. Palatability is an extremely important factor in ensuring the likelihood that the recipients will intake the pharmaceuticals. A constant problem is in treatment of patient is their inability or unwillingness to swallow solid dosage forming such as tablets especially in children and the elderly. These dosage forms permit perceptible exposure of active drug ingredient to the taste bud. Accordingly, masking of unpleasant taste characteristics of drug is an important factor in formulation of these agents. “The worse the taste of the medication, the better the cure” was once the prevailing attitude. Today a change in patient attitude and development of taste masking technique has reversed this opinion. Patients now expect and demand formulations that are pleasantly, or at least tolerably, flavored. This article reviews the earlier methodologies and approaches of taste masking techniques of bitterness reduction.